PENGARUH INVESTMENT OPPORTUNITY SET, PERTUMBUHAN LABA, KONSERVATISME AKUNTANSI, DAN KOMITE AUDIT TERHADAP KUALITAS LABA - Bella Puspitasari; Yuli Tri Cahyono (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to find out and analyze the influence of investment opportunity set, profit growth, accounting conservatism, and audit committee on profit quality. This type of research is quantitative research, the population in this study is the financial statement data of property, real estate, and building construction companies listed on the IDX as many as 109 companies. The sampling method with the purposive sampling method was obtained by 48 companies as samples. Data processing uses multiple linear regression analysis. The results of the data analysis show that accounting conservatism has an effect, while IOS, profit growth, and the audit committee have no effect on profit quality. The results of this study are expected to be considered for evaluation in decision-making, as well as as reference material for future research